#TITLE_ALTERNATIVE# - HANDOYO SAPUTRO (NIM : 23108322); Pembimbing 1 : Dr. Ir. Nathanael P. Tandian; Pembimbing 2 : , DWI
There is waste heat from burning gas to Load Compartment (located in between the turbine and generator), when the PLTGU Tambak Lorok’s gas turbine (GE MS9001E) is operation. The waste heat can be used for other useful purposes. This thesis deals with a preliminary thermoeconomic analysis of three gas turbine waste heat utilization options. Waste heat from a gas turbine is proposed to be utilized by an absorption refrigeration system. The first option is to increase gas turbine output by decreasing the compressor inlet air temperature by using the proposed absorption refrigeration. The second option is to substitute the vapor compression component of nearby building’s HVAC system by the proposed absorption refrigeration. The third option is to increase the CSR program for local communities by producing ice for the local fishermen by utilizing the proposed absorption refrigeration. The initial analysis shows that the second option is the most optimum among the three options studied in this thesis. However, the third option shows an intangible/ social content that will improve the local economy, which is also increasing the corporate image through the KLH’s PROPER program.